2020
DOI: 10.1073/pnas.1916366117
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable nucleation and growth of ultrafine particles from vehicular exhaust

Abstract: High levels of ultrafine particles (UFPs; diameter of less than 50 nm) are frequently produced from new particle formation under urban conditions, with profound implications on human health, weather, and climate. However, the fundamental mechanisms of new particle formation remain elusive, and few experimental studies have realistically replicated the relevant atmospheric conditions. Previous experimental studies simulated oxidation of one compound or a mixture of a few compounds, and extrapolation of the labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 147 publications
(114 citation statements)
references
References 39 publications
7
93
0
Order By: Relevance
“…On the other hand, the correlation between Csulfate/CCO and -CHONO/CCO was much weaker (R=0.26), suggesting a weak connection between particle-phase sulfate and gas-phase H2SO4. This was also consistent with the previous understanding that heterogeneous reactions of SO2 were the dominating pathway for sulfate formation (Zheng et al, 2015a;He et al, 2018;Zhang et al, 2020). Overall, this work well supported the recent modeling results that HONO could obviously promote the aerosol production in winter (Zhang et al, 2019a;Zhang et al, 2019b;Xing et al, 2019;An et al, 2013) from the point of view of observation.…”
Section: Promotion Effect Of Hono Photolysis On Aerosol Formation In supporting
confidence: 92%
See 4 more Smart Citations
“…On the other hand, the correlation between Csulfate/CCO and -CHONO/CCO was much weaker (R=0.26), suggesting a weak connection between particle-phase sulfate and gas-phase H2SO4. This was also consistent with the previous understanding that heterogeneous reactions of SO2 were the dominating pathway for sulfate formation (Zheng et al, 2015a;He et al, 2018;Zhang et al, 2020). Overall, this work well supported the recent modeling results that HONO could obviously promote the aerosol production in winter (Zhang et al, 2019a;Zhang et al, 2019b;Xing et al, 2019;An et al, 2013) from the point of view of observation.…”
Section: Promotion Effect Of Hono Photolysis On Aerosol Formation In supporting
confidence: 92%
“…It was around 2 times compared to places such as Tokyo (Kanaya et al, 2007) and New York City (Ren et al, 2006). A very recent work has found that oxidation of VOCs from local traffic emission is still efficient even under pollution conditions (Guo et al, 2020). This implies that oxidation of atmospheric trace gases by OH may still be highly effective even in wintertime, thereby facilitating the vigorous formation of secondary pollutants in…”
Section: Promotion Effect Of Hono Photolysis On Aerosol Formation In mentioning
confidence: 99%
See 3 more Smart Citations